Regulatory framework of pricing and estimate standards in the petroleum sector; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Romanyuk V. B. Vera Borisovna; Baitova U.; Safronova E.; Pozdeeva G. P. Galina Petrovna (Petroleum Engineering Economics. Mining Law, 2015)
Title screen